POSITION OF THE CITY OFFICIALS AND CIVIL SERVANTS IN THE CITY OF OSIJEK FROM 1918 TO 1934 - Lachner, Višnja (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
In this paper, author discusses and analyzes the normative (legal) regulation of the position of city officials and civil servants, that is, the status and payment system in the Osijek city administration in the period from the emergence of the Kingdom of Serbs, Croats and Slovenes to the promulgation of the Municipalities Act of 1934 (in the interwar period). In covering the topic, the author primarily used the relevant regulations and the archival material available at the State Archives in Osijek. Based on normative analysis and when you take into the consideration the position of city officials and civil servants in the city of Osijek, during the interwar period, in relation to their position during the Austro-Hungarian Empire, it can be stated that according to these Statutes a system of classification of officials was applied, which classified them into types and occupations depending on the level of professional qualifications required to perform them. Until then, the salaries of city employees were regulated by Austro-Hungarian laws, according to which there were wage classes, after which was established a system of dividing payments into basic and position wage, with supplements. As a result, the salaries of city employees are equal to those of state servants. This is a great novelty, because until then the city municipalities had some kind of financial autonomy when determining the level of salaries of city employees. Since then, an evaluation system has been introduced that is directly related to the exercise of individual rights, that is, with the determination of the responsibilities of city employees. The fundamental legal consequences that the Statutes related to the evaluation system concerned the possibility of promotion (to a higher or lower pay grade), termination of service, or loss of a pension. Therefore, it can be concluded that the main purpose of the evaluation was to influence rewards or penalties.